Carbon Accounting and Net Zero 2060: Sustainable Financial Strategies for Achieving the National Carbon Neutrality Target (Literature Review in Indonesia) - Sari, Wa ode Irma; Sahlan, Fahmi; Supriyadi, Supriyadi (STIE Tri Bhakti, 2025)
This study aims to analyze the implementation of carbon accounting and sustainable finance strategies in supporting the achievement of Indonesia’s Net Zero Emissions (NZE) 2060 target. Using a qualitative approach through an exploratory-analytical literature review, this research explores the dynamics of fiscal policies, developments in reporting standards, and the challenges and opportunities within the financial and industrial sectors. The findings showed that regulatory drivers such as carbon taxation, the integration of international standards (TCFD, GRI, ISSB), and sustainable finance initiatives acted as key enablers of carbon reporting practices. However, implementation faced several barriers, including limited literacy, technical capacity gaps, and uneven economic incentives. Carbon accounting was identified not only as a reporting mechanism but also as a strategic tool for improving efficiency, mitigating risks, and enhancing transparency. This study reinforces the relevance of institutional and legitimacy theories in explaining external pressures on corporate behavior and highlights the importance of reducing information asymmetry in agency relationships between businesses and stakeholders. By strengthening regulatory frameworks, literacy, and reporting infrastructure, carbon accounting has the potential to serve as a catalyst in the transition toward a low-carbon economy. These efforts are crucial to achieving the NZE 2060 target in a fair, effective, and knowledge-based manner.